The scientific life of the city of Levantine Tripoli during the nineteenth century AD - Dannoun, Abdallah Samir (Journal of Humanities & Social Sciences, 2025)
This research examines the scientific life of the city of Levantine Tripoli during the nineteenth century (1801-1900AD)(1217-1318AH). Initially, It begins by introducing this city, its geographical location, and brief islamic history. It then discusses the Kuttabs, schools, and foreign missions in this city during the nineteenth century. Finally, it discusses the copyists, printing, press, books, libraries, and authorship movement in Levantine Tripoli during the same period.